TEACHERS’ READINESS TOWARD THE NEW PARADIGM OF ENGLISH LANGUAGE TEACHING: A NARRATIVE INQUIRY - Pujiani, Tri; Sukmawati, Ida Dian; Indrasari, Nunun (UC Journal: ELT, Linguistics and Literature Journal, 2022)
The development of English Language Teaching grows rapidly. The pandemic of Covid-19 became the turning point for teachers' awareness of the need for changes in language teaching practices. The advance in technology also takes an important role in the current trends of Language teaching. A narrative inquiry research method was applied to investigate the teachers' perception of their readiness toward the paradigm shift of English Language Teaching. Eight English teachers from many areas in Indonesia such as Semarang, Lampung, Jombang, Surakarta, Yogyakarta, and Purwokerto participated in this research through in-depth interviews. Then, the data collected were classified into several points regarding the new paradigms of education. The teachers' views on the paradigm shift in Education and the current practice of English Language Teaching were presented in this paper. Finally, teachers as the spearhead of education are required to be lifelong learners who are creative, innovative, and adaptive to the rapid change in world trends.